DFT Predictions of Crystal Structure, Electronic Structure, Compressibility, and Elastic Properties of Hf–Al–C Carbides. Issue 10 (22nd June 2016) - Bai, Yuelei; Duff, Andrew; Jayaseelan, Daniel Doni; Wang, Rongguo; He, Xiaodong; Lee, William Edward
Abstract : To understand the potential for use of the Hf–Al–C ternary compounds, (HfC) n Al3 C2 (Hf2 Al3 C4 and Hf3 Al3 C5 ) and (HfC) n Al4 C3 (Hf2 Al4 C5 and Hf3 Al4 C6 ) were investigated using density functional theory, including crystal structure, electronic structure, compressibility, and elastic properties. The theoretical density of (HfC) n Al3 C2 (4.10–4.16 g/cm 3 ) is higher than that of (HfC) n Al4 C3 (3.92–3.98 g/cm 3 ), due to the smaller number of lighter Al–C layers. With increasing numbers of Hf–C layers, the Hf–C and Al–C bond lengths remain almost unchanged. In none of the compounds is there a gap around the Fermi energy ( E f ), which implies they are metal‐like conductors. With increasing pressure, there is greater shrinkage along the c axis than the a axis. The bond stiffness increases with increasing pressure. In general, (HfC) n Al3 C2 has higher elastic stiffness than (HfC) n Al4 C3, with the moduli increasing with the number of Hf–C layers. The Hf–Al–C compounds as well as the brittle Zr–Al–C compounds all have low shear moduli/bulk moduli ratio ( G / B ) from 0.71 to 0.78, suggesting that the G / B ratio is not always a suitable measure of ductility.